Gereja sebagai Pusat Pendidikan Kristen - Eunike Agoestina (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2022)
The church as a center for Christian education means that the church is a place for education for congregations to learn about Christ and the truth of God's Word, on an ongoing basis from childhood to old age. Lifelong Christian education, carried out regularly, planned, programmed and consistent in its implementation. To realize the church as a center for Christian education, the church needs to establish a vision and goals, organize the management of the implementation of Christian education on a regular basis. The organizational structure of Christian education at a minimum consists of a pastor as the person in charge, chairman, age group coordinator, and administrative staff, Abstrak Bahasa Indonesia Gereja sebagai pusat pendidikan Kristen artinya gereja menjadi tempat pelaksanaan pendidikan bagi jemaat untuk belajar mengenal Kristus dan kebenaran Firman Tuhan, secara berkesinambungan mulai dari usia anak sampai dengan lanjut usia. Pendidikan Kristen sepanjang hayat, dilaksanakan secara teratur, terencana, terprogram dan konsisten dalam pelaksanaannya. Untuk mewujudkan gereja sebagai pusat pendidikan Kristen gereja perlu untuk menetapkan visi dan tujuan, menyelenggarakan pengelolaan pelaksanaan pendidikan Kristen secara teratur. Susunan organisasi pendidikan Kristen minimal terdiri dari pendeta/gembala sebagai penanggungjawab, ketua, koordinator kelompok usia, dan tenaga administrasi,